Differences in Percentage Predicted Spirometric Values Obtained with Thirteen Reference Equations Applied to Healthy Children - Mallol-Villablanca, E; Aguirre-Camposano, V (Taylor and Francis Ltd., 2025)
Background: There is limited information on the discrepancy between the spirometric values calculated with diverse spirometric prediction equations in normal children. Objective: To determine the differences in percentage predicted (PP) values calculated through thirteen prediction equations (PEs) in healthy Chilean children. Methods: We compared the PP values for FVC, FEV1, FEF25–75% and FEV1/FVC obtained by applying thirteen PEs, using GLI-2012 as a gold standard reference equation and including race neutral GLI-2022 in the analysis; PP values are from a group of 208 healthy Chilean children aged 7 to 17 years. Results: In boys, the range of differences for FVC between PEs compared to the reference group went from −5.47% to 20.82% and from −6.4% to 19.74% in girls. For FEV1, in girls, the range of differences went from −5.96% to 18.01% and from −5,04% to 20.67% in boys. Significant differences between GLI-2012 PPs and the other PEs were observed more frequently in girls than in boys (p < 0.001). Conclusions: There is a wide difference between the spirometric PPs values by different PEs, including race neutral GLI-2022. Our findings, especially given the potential interpretative and clinical implications, might suggest the need for conducting standardized, multicenter studies in Latin America to determine which PEs would better fit pediatric populations in this region. © 2024 Taylor & Francis Group, LLC.